Efektivitas Biopestisida Ekstrak Daun dan Kulit Kakao terhadap Mortalitas dan Penghambatan Perkembangan Riptortus linearis - Cindowarni, Olivia (Universitas Muhammadiyah Kotabumi, 2024)
Riptortus linearis is an important pest of soybean plants. An alternative control method that utilizes toxic compounds from plants, known as botanical pesticides or biopesticides. This study aims to determine the effectiveness of cocoa leaf and bark extracts on the mortality and inhibition of the development of R. linearis at various concentrations. The research was conducted in two locations, namely in the experimental garden and at the Laboratory of Universitas Satu Nusa Lampung. The research was conducted over four months from July to October 2024. This experiment consists of seven treatments with three repetitions. The treatments consist of a control treatment or no treatment (B0), 1% cocoa leaf extract (B1), 2% cocoa leaf extract (B2), 3% cocoa leaf extract (B3), 2% cocoa pod husk extract (B4), 4% cocoa pod husk extract (B5), and 6% cocoa pod husk extract (B6). The research results show that the application of cocoa leaf and bark extracts significantly affects the mortality of R. linearis nymphs. The mortality of R. linearis nymphs increased until the end of the observation. Cocoa leaf and bark extracts significantly inhibit the development of R. linearis nymphs, as evidenced by their shorter lifespan and reduced appetite.